THE EFFECTS OF WEANING TIME ON THE GROWTH AND SURVIVAL OF MUD CRAB (Scylla olivacea)THE EFFECTS OF WEANING TIME ON THE GROWTH AND SURVIVAL OF MUD CRAB (Scylla olivacea) - Haryati Haryati; Yushinta Fujaya; Early Septiningsih (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2018)
Live foods such as rotifers and Artemia are commonly used as foods in larval rearing of mud crab (S. olivacea). However, the continuous availability and nutritional consistency of live foods are difficult to control. Thus, the development of artificial diets to partially or fully replaced live foods is needed to overcome the limitations of live foods. The purpose of this research was to determine the best stage at which mud crab larvae can be weaned from live foods to artificial diets. The research experiment consisted of: treatment-1, the larvae were fed with live foods from zoea-1 to megalopa stages as the control treatment; treatment-2, the larvae were fed with artificial diet from zoea-2 to megalopa stages; and treatment-3, the larvae were fed with artificial diet from zoea-3 to megalopa stages. In treatment-4, artificial diet was given from zoea-4 to megalopa stages. The growth and survival rate of larvae in treatment-1, 3, and 4 were not significantly different (P>0.05) but significantly different with treatment-2. Based on the present results, this study suggests that artificial diet can be given to mud crab larvae (S. olivacea) from the third zoea stage.